Lightning phenomena and its effect on transmission line - Agrawal, Swati; Nigam, Manoj Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> As we know that Lightning is one of the most natural and serious cause of over voltage .So, my this paper describes about the lightning phenomena, the way it is caused and in the manner it effects the power equipments, building frames, transmission lines, etc It is matter of great surprise to know that over the whole world ,more than 40,000 lightning strokes per day and less than 100 lightning strokes per second takes place. Transmission lines functions as arteries that carry electricity from power stations to regions where the power is needed. Therefore, it is vital to control the construction and maintenance costs of these lines because while the frequency of transmission line faults resulting in power loss has decreased year by year yet the trouble due to natural cause lightning is not yet reduced The main object of this paper is to study the effect of lightning strokes on transmission lines which cause great damage due to traveling waves to the electrical equipments installed in open air and insulators, etc. Frequently lightning problems do not receive consideration during the design stage. It remains then for the lightning safety engineer to analyze the effect of thelightning during operations and to provide rational for safety through modification to the Assets, Facilities and Structures. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->